An Investigation into the Relationship between Students' Conceptions of the Particulate Nature of Matter and their Understanding of Chemical Bonding - Othman, J.; Treagust, David; Chandrasegaran, Arulsingam (Routledge, 2008)
A thorough understanding of chemical bonding requires familiarity with the particulate nature of matter. In this study, a two-tier multiple-choice diagnostic instrument consisting of ten items (five items involving each of the two concepts) was developed to assess students’ understanding of the particulate nature of matter and chemical bonding so as to identify possible associations between students’ understandings of the two concepts. The instrument was administered to 260 Grades 9 and 10 students (15–16 years old) from a secondary school in Singapore. Analysis of students’ responses revealed several alternative conceptions about the two concepts. In addition, analysis of six pairs of items suggested that students’ limited understanding of the particulate nature of matter influenced their understanding of chemical bonding. The findings provide useful information for challenging students’ alternative conceptions about the particulate nature of matter during classroom instruction in order to enable them to achieve better understanding of chemical bonding.